Assessing upper limb function in multiple sclerosis using an engineered glove. (9th September 2020) - Carmisciano, L.; Signori, A.; Pardini, M.; Novi, G.; Lapucci, C.; Nesi, L.; Gallo, E.; Laroni, A.; Cellerino, M.; Meli, R.; Sbragia, E.; Filippi, L.; et al.
Abstract : Background and purpose: The importance of upper limb function in multiple sclerosis (MS) is increasingly recognized, especially for the evaluation of patients with progressive MS with reduced mobility. Two sensor‐engineered gloves, able to measure quantitatively the timing of finger opposition movements, were previously used to assess upper limb disability in MS. The aims of the present study were: (1) to confirm the association between glove‐derived variables and standard measures of MS disability in a larger cohort; (2) to assess the correlation with quantitative magnetic resonance imaging (MRI) and quality of life (QoL) measures; and (3) to determine if the glove‐derived variables offer advantages over the standard measure for assessing upper limb function in MS, namely, the Nine‐Hole Peg Test (9HPT). Methods: Sixty‐five patients with MS, stable on disease‐modifying treatment, were evaluated at baseline using the glove, and through clinical examination (Expanded Disability Status Scale, Symbol Digit Modalities Test, Timed 25‐Foot Walk Test and 9HPT), MRI evaluation and QoL questionnaires. Correlations between the glove‐derived variables and clinical, MRI and QoL variables were assessed using Spearman's rank correlation coefficient analysis. Results: Glove‐derived variables significantly differed between patients with relapsing‐remitting and those with progressive MS, with similar or slightly higher correlations of the 9HPT with clinical variables. We found greater correlations of the QoL physical component with glove‐derived variables than with the 9HPT, and a significant correlation of its mental component with the glove‐derived variables but not with the 9HPT. Conclusion: The study results, confirming previous findings and showing advantages over the 9HPT, encourage the investigation of sensitivity to change in glove‐derived variables in a longitudinal setting.